Resource Conservation, Environmental Preservation, and the Rate of Discount - Fisher, Anthony C.; Krutilla, John V. (Quarterly Journal of Economics, 1975)
I. Discounting and conservation, 359. — II. A model for natural environmental resource allocation: the concept of effective discount rates, 362. — III. Concluding remarks, 370.